2017
DOI: 10.17265/1934-8975/2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Temperature Distributions in Single Cell of Polymer Electrolyte Fuel Cell when Operated in Elevated Temperature Range

Abstract: Abstract:The purpose of this study is to analyze the temperature distribution on the interface between the polymer electrolyte membrane and catalyst layer at the cathode in single cell of polymer electrolyte fuel cell when operated in elevated temperature range than usual. In this study, the interface between the polymer electrolyte membrane and catalyst layer at the cathode is named as reaction surface. This study has considered the 1D multi-plate heat transfer model estimating the temperature distribution on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…However, we have confirmed the temperature gradients for the targeted regions are almost the same tendency under the similar operational conditions [42]. In addition, the authors [43] have already simulated by the commercial CFD software with 3D model in order to predict the distributions of T react . This 3D model bases on the governing equations consisting of conservation equations of mass, momentum, energy in porous region and electro-chemical reaction.…”
Section: Validationsupporting
confidence: 67%
“…However, we have confirmed the temperature gradients for the targeted regions are almost the same tendency under the similar operational conditions [42]. In addition, the authors [43] have already simulated by the commercial CFD software with 3D model in order to predict the distributions of T react . This 3D model bases on the governing equations consisting of conservation equations of mass, momentum, energy in porous region and electro-chemical reaction.…”
Section: Validationsupporting
confidence: 67%
“…Consequently, we can ignore the impact of the observation window on the power generation performance. In addition, we estimated the in-plane temperature distribution on the interface between PEM and cathode catalyst layer using the temperature data measured by thermograph and the proposed heat transfer model, and compared with the temperature distribution calculated by 3D numerical simulation considering the electrochemical reaction, fluid dynamics, heat transfer and gas diffusion [29]. As a result, the maximum and the minimum temperature difference between these studies was 0.7 • C and 0.1 • C respectively for anode 80% RH and cathode 80% RH at T ini = 90 • C. Additionally, the tendency of in-plane temperature distribution was almost similar, e.g., the temperature rise and drop were observed at the same points, respectively, among these studies.…”
Section: Experimental Set-up and Proceduresmentioning
confidence: 99%
“…However, it can be observed that the temperature gradients, for the targeted regions under similar operation conditions, show the same tendency [39]. In addition, the authors [40] have already studied the numerical simulation using a 3D model, by means of commercial CFD software, in order to predict the distributions of T react . This numerical simulation, with a 3D model, considers the governing equations that consist of conservation equations of mass, momentum, and energy in the porous region as well as the electrochemical reaction.…”
Section: Validationmentioning
confidence: 98%